LITERATURE STUDY ANALYSIS OF BUSINESS INTELLIGENCE RESEARCH APPLICATIONS FOR DECISION-MAKING - Heripracoyo, Sulistyo (Proceedings of KNASTIK, 2012)
Application of Data Warehouse (DW) and Business Intelligence (BI), is an application that can be implemented by various companies to implement strategies to compete and benefit for organization generally will be effective and efficient operation of itsbusiness. This paper is an analysis of research results from the application of Business Intelligence and DW-related decision-making system. In this paper the focus of the analysis are a variety of Business Intelligence applications, how BI applications can affect the performance of the company / organization, how far the BI application is received by the organization, what decisions can be supported by BI, how many decisions can be taken from the BI application, how good the decision of BI applications, BI applications are applicable to various organizations / companies, allthe data to answer some of these problem from the previous research / literature. The result is a BI application analysis and comparison and criticism of previous studies.